The Effect of The PBL Model with The JAS Approach on Students' Scientific Literacy Skills in The Excretory System Materials - Cahyani, Fitri; Marianti, Aditya (Journal of Biology Education, 2021)
This study was aimed at analyzing the effect of the PBL model with the JAS approach on students' scientific literacy skills in the excretory system materials. The study was conducted at SMA Negeri 2 Semarang in the second semester in the academic year of 2019/2020. The population of this research were the eleventh grade science students of SMA Negeri 2 Semarang in the academic year of 2019/2020. The sampling technique used was simple random sampling, in which the class used in this study was randomly chosen by the researcher. In this study, class of XI MIA 3 that consisted of 36 students selected as the control class while XI MIA 2 class with 36 students selected as the experimental class. The research design used on this study was Pretest-Posttest Control Group Design. The data in this study were in the forms of the results of tests of students' scientific literacy skills, observation of students' scientific competencies, the implementation of learning syntax, and students' responses to learning. Independent sample t-test results showed Sig. (2-tailed) < 0.05, it could be meant that there were differences in the ability of scientific literacy between the experimental class and control class after learning. The implementation of learning was equal to 92% that fell into high category. Based on the results of this research, it was able to be concluded that the Problem Based Learning model with the JAS approach affected the ability of students' scientific literacy in the excretion system materials.